Academic Freedom at the Crossroads in the United States - Benedict, Louis (International Higher Education, 2009)
Academic freedom in the United States has long been associated with the values inherent in the First Amendment free-speech clause of the US Constitution. In recent years a deterioration of academic freedom has occurred in higher education institutions in the United States. Exacerbating this trend is that US courts, longstanding protectors of the value of free speech, have whittled away some of the traditional academic freedom protection afforded to faculty at public colleges and universities. Several factors have contributed to a general decline in protection of academic freedom, such as the events of 9/11, the mis-application of the business model for higher education, and recent US Court decisions regarding academic freedom. These factors threaten the future viability of academic freedom and the advantages to higher education and society.